Association of plasma fibrinogen level with the severity of obstructive sleep apnoea patients in a tertiary care hospital - Alam, M. Shariful; Tanimul Haque Rijvy, M.; Dip, Abir H.; Quadry, Shafiul A.; Dhar, Uma; Mosharraf Hossain, A. K. M.; Islam, Samprity; Rahim, Abdur; Chakrabortty, Rajashish; Paul, Susanto K. (International Journal of Research in Medical Sciences, 2024)
Background: Obstructive sleep apnoea syndrome (OSAS) is a common sleep-related breathing disorder of multi-risk factorial pathogenesis and is characterized by recurrent, partial or complete upper airway obstruction resulting in intermittent hypoxia during sleep. It has been implicated in both cardiovascular and cerebrovascular diseases. Objective of the study was to determine the association of Plasma Fibrinogen levels with the severity of OSA patients in a tertiary care hospital. Methods: This cross-sectional observational study with group comparison was conducted among all the patients attending in the Department of Respiratory Medicine, BSMMU with suspicion of OSA within one year after the clearance of institutional review board (IRB) using STOP-BANG questionnaire and Epworth sleepiness scale (ESS) and confirmed by polysomnography. Plasma fibrinogen was measured in all OSA and non-OSA patients. Data were analyzed with the help of statistical package for the social sciences (SPSS) version 26. Results: Sociodemographic analysis found no significant differences in age, gender, area, occupation, or smoking between OSA and non-OSA groups (p>0.05). However, witnessed apnoea (p=0.002), breathlessness (p=0.005), higher ESS (p<0.001), and STOP-Bang scores (p<0.001) were associated with OSA. Plasma fibrinogen levels were significantly higher in OSA (319.2±63.7 mg/dl versus 242.5±20.33 mg/dl, p<0.001), positively correlating with AHI (r=+0.876, p=0.001). Positive correlations were also found between fibrinogen levels and daytime sleepiness (r= +0.393, p=0.002), waist circumference (r =+0.346, p=0.007), and BMI (r =+0.297, p=0.021) in OSA patients. Conclusions: In conclusion, this study establishes a notable connection between plasma fibrinogen levels and the severity of OSA. Elevated fibrinogen levels correlate with increased OSA severity, indicating a link between OSA, inflammation and coagulation.